Answer:
[tex](-\frac{7}{13},\frac{79}{13})[/tex]
Step-by-step explanation:
Given:
Two equations are given.
[tex]- 7x + 3y = 22[/tex]------(1)
[tex]4x + 2y = 10[/tex]----------(2)
Solve equation 1 for y.
[tex]- 7x + 3y = 22[/tex]
[tex]3y = 22+7x[/tex]
[tex]y=\frac{22+7x}{3}[/tex]-----------(3)
Now, we substitute y value in equation 2.
[tex]4x + 2(\frac{22+7x}{3}) = 10[/tex]
[tex]\frac{12x + 2(22+7x)}{3} = 10[/tex]
[tex]12x + 2(22+7x)=10\times 3[/tex]
[tex]12x + 44+14x=30[/tex]
[tex]26x=30-44[/tex]
[tex]26x=-14[/tex]
[tex]x=-\frac{14}{26}[/tex]
[tex]x=-\frac{7}{13}[/tex]
Now, we substitute x value in equation 1.
[tex]- 7(-\frac{7}{13}) + 3y = 22[/tex]
[tex]\frac{7\times 7}{13} + 3y = 22[/tex]
[tex]\frac{49}{13} + 3y = 22[/tex]
[tex]3y = 22-\frac{49}{13}[/tex]
[tex]3y = \frac{13\times 22-49}{13}[/tex]
[tex]3y = \frac{286-49}{13}[/tex]
[tex]y = \frac{237}{13\times 3}[/tex]
[tex]y = \frac{237}{39}[/tex]
[tex]y = \frac{79}{13}[/tex]
Therefore, the value of x and y is [tex](x=-\frac{7}{13},y = \frac{79}{13})[/tex]